Adjuvant-induced autoimmune syndrome triggered by silicone breast implants: systematic review - Caio Munaretto Giacomazzo; Caroline Noda Sakai; Rayane Merlly Gandolfi de Araujo; Maria Cecilia Closs Ono; Alfredo Benjamin Duarte-da-Silva; Renato da Silva Freitas (Revista Brasileira de Cirurgia Plástica)
Adjuvant-induced autoimmune syndrome (ASIA) and its diagnostic criteria were described by Shoenfeld in 2011, relating symptoms of autoimmunity to adjuvants, such as silicone, present in breast implants. This systematic review aimed to gather data from the literature on symptomatology, incidence and proposed treatments for ASIA caused by silicone breast implants (SBI). Searches were carried out in PubMed, LILACS, Embase and Cochrane databases, using the descriptors “Autoimmune Syndrome Induced by Adjuvants,” “Breast implant,” and “Silicone Implant Incompatibility Syndrome.” The search strategy generated 95 articles, of which 20 were included in the review. The authors suggest three main theories to explain the development of the syndrome: genetic predisposition, silicone bleeding and the formation of a periprosthetic capsule. The most frequently described clinical manifestations include chronic fatigue, arthralgia, myalgia, and cognitive and sleep disorders. There is no consensus on laboratory findings and associated risk factors; recent studies propose expanding the diagnostic criteria initially described. Adequate treatment remains controversial, ranging from medications to prosthesis explantation. Although the reviewed articles suggest the existence of ASIA related to SBI, its precise pathophysiology is unknown, the symptoms reported are nonspecific, and the time between exposure and the onset of manifestations is uncertain. This systematic review concludes that, to date, there is not enough scientific evidence to establish the causality of the development of adjuvant-induced autoimmune syndrome resulting from silicone breast implants.